A facile route to realize ultraviolet emission in a nano-engineered SnO2-based light-emitting diode. (20th October 2015) - Huang, Yanan; Li, Yongfeng; Yao, Bin; Ding, Zhanhui; Deng, Rui; Zhang, Ligong; Zhao, Haifeng
Abstract: We reported a facile route to fabricate a tin dioxide (SnO2 )-based light-emitting diode (LED) and obtain an electrically pumped band-edge ultraviolet (UV) emission. We first investigated the photoluminescence (PL) properties of the SnO2 thin films deposited on quartz substrates annealed at various temperatures. It was found that SnO2 nanocrystals were embedded in the SnO2 amorphous matrix after annealing at 400 °C to form a SnO2 nanoparticle/amorphous hybrid film; the band-edge UV emission was observed from the hybrid film due to the hybrid structure breaking the dipole-forbidden rule of bulk SnO2 . This hybrid SnO2 film was then deposited on a p-type GaN substrate to form a SnO2 hybrid film-based LED and a band-edge UV electroluminescence (EL) was observed. Our results suggest that this easy and effective approach may find extensive application in the field of optoelectronics, displays and solid-state lighting.